Pengaruh Label Halal dan Kualitas Produk Terhadap Proses Keputusan Pembelian Kosmetik Merek Wardah dengan Menggunakan Brand Image Sebagai Variabel Intervening - Wanda Gema Prasadio Akbar Hidayat (Sekolah Tinggi Agama Islam Taruna Surabaya, 2023)
This research is descriptive and causal research. Sampling technique in this study was purposive sampling. The number of samples in this study as many as 100 people. This study used a questionnaire instrument. This study uses the PATH Statistical Analysis tools. The results showed that the labeling of halal and quality products together (simultaneously) to the brand image has a strong relationship or positive, and partially labeled halal significant effect on brand image. Brand image of the purchase decision process there is a strong relationship. Halal label and product quality together (simultaneously) the purchase decision process also has a strong relationship or positive, and partially significant effect on the quality of the product purchase decision process. Halal label and product quality together (simultaneously) the purchase decision process through brand image also have a strong relationship or positive, and partially significant effect on the quality of the product purchase decision process through brand image.